Gum katira-silver nanoparticle-based bionanocomposite for the removal of methyl red dye - Saruchi,; Kumar, Vaneet; Bhatt, Diksha; El-Serehy, Hamed A.; Pandey, Sadanand (Frontiers in Chemistry, 2023)
The present work envisaged synthesizing Gum katira-silver nanoparticles based bionanocomposite. Different characterization techniques were used to analyze the synthesized bionanocomposite such as Fourier transform infrared (FTIR) spectroscopy, Field Emission scanning electronmicroscopy (FESEM), thermo-gravimetric analysis (TGA) and Transmission Electronic Microscopy (TEM). AgNPs were formed having sizes in the range of 6-20 nm. TGA showed that synthesized nanocomposite are thermally more stable than Gum katira. All the reaction conditions such as time, temperature, pH, solvent, amount of nanoparticles, the concentration of initiator, cross-linker, and monomer were optimized with respect to swelling. The result showed that the highest percentage swelling (Ps) of Gk-cl-poly(AA) was 796% and AgNPs imbibed Gk-cl-poly(AA)-AgNPs was 867%. Synthesized bionanocomposite was utilized as an adsorbent material for the adsorption of methyl red (MR) dye. Effects of different reaction conditions were also optimized, so as to attain the utmost adsorption of MR dye. Utmost dye adsorption through Gk-cl-poly(AA)-AgNPs bionanocomposite was 95.7%. Diverse kinetics and isotherms models were used to study the adsorption data. The R2 value was established to be 0.98783 and was determined to be 0.02671. As the value of second order kinetics is greater than first order kinetics, it suggests that methyl red adsorption by nanocomposite is best explained by pseudo second order kinetics, which indicated that dye adsorption occurred through chemisorption. R2 was determined to be 0.9954. Correlation coefficient values of Gk-cl-poly(AA)-AgNPs were best fitted to the Freundlich adsorption isotherm. Synthesized bionanocomposite was acting as a proficient material for the removal of MR dye from wastewater.